Protein kinase Cγ mediates ethanol withdrawal hyper-responsiveness of NMDA receptor currents in spinal cord motor neurons - Li, Hui-Fang (2005)
1. The present studies were designed to test the hypothesis that neuronal-specific protein kinase Cγ (PKCγ) plays a critical role in acute ethanol withdrawal hyper-responsiveness in spinal cord. 2. Patch-clamp studies were carried out in motor neurons in neonatal rat spinal cord slices. Postsynaptic currents were evoked by brief pulses of 2 mM N-methyl-D-aspartic acid (NMDA) in the presence of bicuculline methiodide 10 μM; strychnine 5 μM and tetrodotoxin 0.5 μM. 3. Both ethanol depression and withdrawal hyper-responsiveness of NMDA-evoked currents are dependent on increases in intracellular Ca(2+). Blocking intracellular increase in Ca(2+) by 30 mM 1,2-bis(2-aminophenoxy)-ethane-N,N,N′,N′-tetraacetic acid (BAPTA) not only decreased the ethanol-induced depression of NMDA-evoked currents (33±5% in control vs 20±3% in BAPTA, P<0.05) but also eliminated acute ethanol withdrawal hyper-responsiveness. 4. Immunohistochemistry studies revealed that neonatal spinal cord motor neurons contain an abundance of nuclear PKCγ. 5. Exposure to ethanol (100 mM) induced PKCγ translocation from the nucleus to cytoplasm in motor neurons. Pretreatment with the γ-isozyme-specific peptide PKC inhibitor, γV5-3, blocked ethanol-induced translocation and also blocked withdrawal hyper-responsiveness. 6. The results show that PKCγ mediates ethanol withdrawal hyper-responsiveness in spinal motor neurons; the results may be relevant to some symptoms of ethanol withdrawal in vivo.